(untitled) (Papeles, 2024)
Scientific publications assume a superlative role for the production and circulation of knowledge developed by researchers. Likewise, they are the main devices recovered in the evaluation of the academic quality in institutions/organizations and people. However, within the borders of the World Academic System, they are valued in a differential way, accumulating disparate prestige quotas according to their language, transit through circulation circuits and institutions and geographical regions where their publishers are located. All this impacts on different decisions addressed by researchers when publishing their results. This article focusses in how Argentine scientists assume certain modes of circulation of their publications according to the transit through indexing databases, their disciplines, as well as their co-authorship options. In line with the PISAC-STI framework project, the article is conceptually based on the paradigm of the circulation of knowledge and methodologically stands as a synchronous-descriptive case study focused on twelve Argentine National Universities. Among its main findings, it accounts for the existence of profiles that crystallize various modes of internationalization which are questioned by disciplines, indexing and inter-institutional collaboration.